Quintuple Helix Model: Investment Aspects of Higher Education Impact on Sustainability - Kholiavko, N; Grosu, V; Safonov, Yu.; Zhavoronok, A; Cosmulese, C.G. (Management Theory and Studies for Rural Business and Infrastructure Development, 2021)
The interdisciplinary analysis of sustainability requires an in-depth study ofinteractions between different economic entities, and identifying investment aspects of developing relations between them. The concept of Quintuple Helix Model allowed to analyze the interactions and mutual influence between universities, industry (business), government, civil society and the natural environment.Withinthe Quintuple Helix Model, the central role in the development of the economy is given to knowledge and their transfer between the various subsystems of the Model. The higher education subsystem occupies a special place in the Model because of suchreasons: 1) withinthe educational activity, universities train highly qualified personnel for thenational economy; 2) within the extracurricular activity, universities develop new green consciousness of the young generation that is crucial for further sustainable development of the national economy; 3) within the research activity, universities develop innovative regenerative technologies and environmental-friendly technologies. Universitiesprovide the generation, transfer and diffusion of sustainable knowledge in society and business. Synergy of higher education (universities), business (industry),government, public (civil society) is able to create a foundation for sustainable development of the national economy, increase the level of environmental protection, reducethe CO2emissions, ensure rational use of exhaustive resources, create new green products and raise the standard of living of the country's population.
Keywords: higher educationsystem, investment,Quintuple Helix Model, sustainability, Sustainable Development Goals.